The perception of job insecurity and organizational citizenship behavior during COVID-19: the moderating roles of positive psychological capital and grit - Farroukh, Nataly (2023)
Purpose In light of COVID-19 and its subsequent disruptions, along with simultaneous changes and transformations taking place, job insecurity (JI) is significantly heightened among employees. This study aims to analyze how JI influences employees’ organizational citizenship behaviors (OCBs) and whether positive psychological capital (PsyCap) and grit moderate this relationship. Design/methodology/approach To test the study hypotheses, data was gathered during COVID-19 via convenience sampling. The collected data was analyzed using the Statistical Package for the Social Sciences software and Excel MegaStat. Findings The empirical data shows that qualitative JI has a negative relationship with OCB. PsyCap and grit moderate the relationship between both JI dimensions and OCB. Practical implications Managers can alleviate JI in the workplace by promoting PsyCap and grit among employees, both of which will sustain and promote OCB, even during difficult times. Originality/value This study bridges the gap in the literature regarding the impact of JI on employees’ OCB during the pandemic. This study also adds to the limited number of studies exploring personal resources as potential moderators between JI and organization citizenship behavior.